The power unto glory: a Bonaventurean critique of Foucault's critique of power - Giltner, T. Alexander (Scottish journal of theology, 2019)
This article puts Michel Foucault's conception of power into critical engagement with that of Bonaventure. For Foucault power is manifested in wills to knowledge or meaning-making in a senseless universe in order to legitimate the drama of dominations. Bonaventure, however, roots his notion of power in the essence of God, so that any act of power from God cannot be classified as domination, but rather donation - a free-willed gift. This is especially evident in Bonaventure's theology of creation and sacrament. As such, Bonaventure provides a way to deal with Foucault's critique theologically without dispensing with it altogether.